The Role of Employee Engagement in Improving Organizational Performance: A Systematic Literature Review of Human Resources - Hadita Hadita; Didin Sjarifudin; Raihan Saputra; Primadi Candra Susanto (Socrates: Journal of Education, Philosophy and Psychology, 2026)
Employee engagement has become one of the most important topics in human resource management because of its contribution to organizational success. Engaged employees demonstrate high levels of energy, dedication, and absorption in their work, enabling them to contribute more effectively to organizational goals. This study aims to review the role of employee engagement in improving organizational performance through a literature review approach. The study analyzes previous research published in reputable journals indexed by Google Scholar and Scopus. The findings indicate that employee engagement positively influences organizational performance through increased productivity, job satisfaction, organizational commitment, innovation, teamwork effectiveness, and employee retention. Employees with high engagement levels are more likely to demonstrate proactive behavior, share knowledge, collaborate effectively, and contribute beyond their formal job responsibilities. Conversely, low employee engagement is associated with reduced motivation, lower productivity, increased absenteeism, burnout, and higher turnover intentions, all of which negatively affect organizational performance. The review also identifies several factors influencing employee engagement, including leadership, organizational culture, work environment, job characteristics, and human resource management practices. The findings suggest that organizations should prioritize employee engagement strategies to strengthen workforce commitment and achieve sustainable organizational performance. Therefore, employee engagement can be considered a strategic organizational resource that contributes significantly to long-term competitiveness and organizational success.